A simple THD minimization technique for transistor-clamped H-bridge-based cascaded multilevel inverter - Halim, Wahidah Abd; Rahim, Nasrudin Abd; Alias, Azrita (Universiti Teknikal Malaysia Melaka, 2018)
This paper presents a simple modulation technique that minimizes the output voltage total harmonic distortion (THD) without eliminating the lowest order harmonics. It uses the voltage-angle equal concept of sinusoidal reference waveform to generate the step output voltage of a single-phase transistor-clamped H-bridge (TCHB)-based cascaded multilevel inverter. The real implementation of the modulation technique for a various range of modulation indices is built using an Altera field-programmable gate array (FPGA). It is found that the proposed modulation method resulted in a dramatic decrease in the inverter’s output voltage THD when increasing the number of output steps up to thirteen levels.